Interview with Louise Evans and Jonathan Edwards, Gresford, Wales, 28 September 2013 - Messham-Muir, Kit (2014)
Louise Evans – aka. Felt Mistress – creates 3D monster characters that straddle to boundaries of art, pop culture and commercial art. She collaborates closely with long-time partner, Jonathan Edwards, an illustrator and comic artist whose work is often scene illustrating The Guardian. Both live in Gresford, North Wales, near the town of Wrexham. I first met Louise when we were about 9 years old, and Jonathan a few years later in Ysgol Bryn Alyn High School. As a teenager, Jonathan was clearly a talented draughtsman, creating caricatures of me and my friends. I hadn’t seen either Jonathan or Louise for about 25 years, so it was great to catch up with them and discuss their collaboration on Felt Mistress. In Part 1 of this three-part interview, we discuss how both Jonathan and Louise forged their careers over the last 25 years, and consider the advantages, and disadvantages, of practicing in regional UK. Dr Kit Messham-Muir The University of Newcastle